1991
DOI: 10.2307/5450
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Performance in the Western Gull: Effects of Parental Age, Timing of Breeding and Year in Relation to Food Availability

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. British Ecological Society is collaborating with JSTOR to digitize, preserve and extend access to Journal of Animal Ecology. SUMMARY(1) We studied age-specific breeding succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
4

Year Published

1993
1993
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(118 citation statements)
references
References 35 publications
3
110
4
Order By: Relevance
“…Survival times of chicks increased significantly after capelin arrival, and mean nest shift durations compared more closely to those observed in other studies, indicating that food was adequate at that time. Delayed capelin arrival in 1992 resulted in a reversal of the relationship normally observed between early breeding and success, which has been attributed to age and experience (Coulson & White 1958, Montevecchi 1978b, Ryder 1980, Nelson 1988, Sydeman et al 1991. Although early breeders hatched more eggs than late breeders in 1992, late breeders raised more chicks (see also Hatch 1990).…”
Section: /-'---Lmentioning
confidence: 99%
“…Survival times of chicks increased significantly after capelin arrival, and mean nest shift durations compared more closely to those observed in other studies, indicating that food was adequate at that time. Delayed capelin arrival in 1992 resulted in a reversal of the relationship normally observed between early breeding and success, which has been attributed to age and experience (Coulson & White 1958, Montevecchi 1978b, Ryder 1980, Nelson 1988, Sydeman et al 1991. Although early breeders hatched more eggs than late breeders in 1992, late breeders raised more chicks (see also Hatch 1990).…”
Section: /-'---Lmentioning
confidence: 99%
“…STUDIES OF age-related parental changes in reproductive success of many avian species have shown that older individuals nest earlier in the season, produce larger clutches, and have greater fl edging success than do younger conspecifi c individuals (Newton 1979, Saether 1990, Wooller et al 1990, Hamer and Furness 1991, Sydeman et al 1991, Desroschers 1992, Hepp and Kennamer 1993, Forslund and Pärt 1995. Understanding how age infl uences breeding success is important to studies of population dynamics and to our understanding of the relationship between habitat and productivity.…”
mentioning
confidence: 99%
“…Sydeman et al 1991, Svensson & Nilsson 1995, Brodmann et al 1997, Siikamäki 1998, Diaz & Alonso 2003, Rubenstein & Wikelski 2003, Davis et al 2005, Nielsen & Møller 2006, Varpe et al 2007). This difference may be due to the importance of life history timing relative to the physical cycles in the intertidal zone.…”
Section: Discussionmentioning
confidence: 99%
“…Resale or republication not permitted without written consent of the publisher Sydeman et al 1991, Svensson & Nilsson 1995, Brodmann et al 1997, Siikamäki 1998, Rubenstein & Wikelski 2003, Davis et al 2005, but see Shultz et al 2009). Earlier reproduction is thought to enhance food intake rates and the competitive ability of offspring.…”
Section: Abstract: Reproductive Timing · Intertidal Animal · Tidal Rmentioning
confidence: 99%